2021
DOI: 10.1002/cbic.202100533
|View full text |Cite
|
Sign up to set email alerts
|

Strong and Specific Recognition of CAG/CTG Repeat DNA (5’‐dWGCWGCW‐3’) by a Cyclic Pyrrole‐Imidazole Polyamide

Abstract: Abnormally expanded CAG/CTG repeat DNA sequences lead to a variety of neurological diseases, such as Huntington's disease.Here, we synthesized a cyclic pyrrole-imidazole polyamide (cPIP), which can bind to the minor groove of the CAG/CTG DNA sequence. The double-stranded DNA melting temperature (T m ) and surface plasmon resonance assays revealed the high binding affinity of the cPIP. In addition, next-generation sequencing showed that the cPIP had high specificity for its target DNA sequence.Although DNA repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 23 publications
0
14
1
Order By: Relevance
“…Adaptedunder the terms of the Creative Commons CC BY license. [ 102 ] Copyright 2021 The Authors, published by Wiley‐VCH.…”
Section: Targeting Trinucleotide Disorders To Treat Complex Diseasesmentioning
confidence: 99%
See 3 more Smart Citations
“…Adaptedunder the terms of the Creative Commons CC BY license. [ 102 ] Copyright 2021 The Authors, published by Wiley‐VCH.…”
Section: Targeting Trinucleotide Disorders To Treat Complex Diseasesmentioning
confidence: 99%
“…designed and synthesized cyclic (cPIP 1) and hairpin (hPIP 2) versions of PIPs targeting the 5’‐WGCWGCW‐3’ sequence (Figure 5B). [ 102 ]…”
Section: Targeting Trinucleotide Disorders To Treat Complex Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, β-alanine increases the flexibility of PIP and is sometimes used in place of Py; Py−β and β–β pairs recognize A–T or T–A pairs . Using this sequence specificity, many studies have been conducted using various PIPs as drug candidates, , to visualize telomere, , and as epigenetic regulators. A cyclic-PIP (cPIP) that strongly binds to a sequence containing CAG/CTG repeats (5′-WGCWGCW-3′, W: A or T) has been developed . Furthermore, biological experiments using this cPIP revealed that it specifically binds to the hairpin structure that contains the mismatched base pairs formed thereby suppressing the genes that cause the expanded-repeat-associated diseases .…”
Section: Introductionmentioning
confidence: 99%